Sistem Pengelolaan Data Inventaris Universitas Almuslim Berbasis Web - Iqbal Iqbal (Jurnal Tika, 2021)
Procurement of goods and services at Almuslim University is a procurement activity that is financed with development costs or grants from the government, whether carried out independently or by providers of goods. Inventory of goods is a step to carry out data collection and management of assets belonging to Almuslim University as assets. This information system was developed for the management of Almuslim University inventory data where goods are imported and goods are sent out. Information systems in an organization are usually developed to facilitate the management of data that can be obtained, costs for procurement, processing and storage and so on. A computer-based information system is usually used to reduce management costs while increasing the capabilities and performance of information systems. The programming language used is PHP and MySQL as database support